2012
DOI: 10.1371/journal.pone.0044763
|View full text |Cite
|
Sign up to set email alerts
|

Ontogeny of Toll-Like Receptor Mediated Cytokine Responses of South African Infants throughout the First Year of Life

Abstract: The first year of life represents a time of marked susceptibility to infections; this is particularly true for regions in sub-Saharan Africa. As innate immunity directs the adaptive immune response, the observed increased risk for infection as well as a suboptimal response to vaccination in early life may be due to less effective innate immune function. In this study, we followed a longitudinal cohort of infants born and raised in South Africa over the first year of life, employing the most comprehensive analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
50
2
1

Year Published

2012
2012
2025
2025

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(57 citation statements)
references
References 43 publications
4
50
2
1
Order By: Relevance
“…In support of this hypothesis, there is a significant difference in T helper (Th)1 cytokine responsiveness to classical TLR agonists in children from poor regions of South Africa as compared to Canadian children [37]. Most strikingly, immune cells in the blood of South African infants aged 2 years are severely hyporesponsive to lipopolysaccharide (LPS) stimulation and secrete low levels of cytokines in response to TLR4 stimulation compared to age-matched children from Canada [38].…”
Section: Microbiota Speciesmentioning
confidence: 97%
“…In support of this hypothesis, there is a significant difference in T helper (Th)1 cytokine responsiveness to classical TLR agonists in children from poor regions of South Africa as compared to Canadian children [37]. Most strikingly, immune cells in the blood of South African infants aged 2 years are severely hyporesponsive to lipopolysaccharide (LPS) stimulation and secrete low levels of cytokines in response to TLR4 stimulation compared to age-matched children from Canada [38].…”
Section: Microbiota Speciesmentioning
confidence: 97%
“…The completed phase III trial showed only modest efficacy, with an overall 30% protection against severe malaria. 7 Past studies emphasized the gradual acquisition of TLR responsiveness in newborns and infants in whole blood and PBMCs, 8,9 with an age-dependent maturation of IL-12p70 secretion capability throughout childhood. 10 These studies also show that neonatal immune cells seem to produce more IL-10 and T H 17-polarizing cytokines (IL-6, IL-1B, and IL-23) after TLR stimulation.…”
mentioning
confidence: 99%
“…The question remains as to whether or not subsequent seropositivity against pertussis or any other pathogen equates to actual protection against the disease. 24,[28][29][30] The assay that was used in this study was unable to distinguish between IgG antibodies produced as a result of primary infection or vaccination. Furthermore, while PT is exclusively secreted by B. pertussis, FHA is also secreted by B. parapertussis and B. bronchiseptica.…”
Section: Discussionmentioning
confidence: 95%